The Insulin Resistance Intervention after Stroke trial: a perspective on future practice and research - Bath, Philip M.W.; Appleton, Jason P.; Sprigg, Nikola (SAGE Publications, 2016)
The prevention of recurrent events after ischaemic stroke and transient ischaemic attack is well established and based on lifestyle changes, antithrombotics, statins, antihypertensives and carotid surgery. The international IRIS trial assessed whether pioglitazone, a glucose-lowering insulin-sensitizing drug, would reduce recurrent vascular events in patients with ischaemic stroke or transient ischaemic attack. After 4.8 years, pioglitazone therapy was associated with reduced vascular events and new diabetes, and an increase in weight, oedema and bone fractures. Pioglitazone may add to the strategies for preventing further events in patients with stroke or transient ischaemic attack.